Peran Masyarakat dalam Upaya Pelestarian Hutan Taman Nasional Bali Barat di Desa Eka Sari - Ni Putu Eka Dharma Yanti; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2022)
The role of the community in the management of the West Bali National Park Conservation area is to actively involve the community in the management of the Conservation area. Ekasari Village is one of the supporting villages for the West Bali National Park Center. This research examines two things: The role of the community in preserving the forests of the West Bali National Park in Ekasari Village and the Application of Legal Sanctions If People Do Violations. The purpose of this research was to determine the role of the community in forest conservation. This research is an empirical research writing and a sociological approach, the legal materials are sourced from primary legal materials with descriptive data analysis. The results showed that the role of the people of Ekasari Village played an active role in the preservation of the West Bali National Park. If members of the Ekasari Village community commit a violation, they will be subject to sanctions according to what is stipulated in the customary village awig-awig. In addition, sanctions are imposed on Law No. 5 of 1990 Violation of the above provisions can be subject to criminal penalties